2015
DOI: 10.1002/2014ja020387
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale equatorial electrojet turbulence:Baseline 2‐D model

Abstract: The spatial and spectral characteristics of the turbulent plasma density, electric fields, and ion drift in ionospheric E region are studied using a new set of nonlinear plasma fluid equations. The fluid model combines both Farley-Buneman (Type-I) and Gradient-Drift (Type-II) plasma instabilities in the equatorial electrojet. In our unified model of the plasma instabilities, we include the ion viscosity in the ion momentum equation and electron inertia in the electron momentum equation. These two terms play an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 58 publications
1
33
0
Order By: Relevance
“…Moreover, the Doppler shift of Type I irregularities supports the previous observations by Pfaff et al [, ], Kudeki et al [], and Hysell and Burcham [] about the limit of small structure drifts to the ion‐acoustic speed ( C s ). The simulation results of the unified fluid model presented in the previous work [ Hassan et al , and Hassan , ] and the present work show a very good agreement with these radar measurements.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, the Doppler shift of Type I irregularities supports the previous observations by Pfaff et al [, ], Kudeki et al [], and Hysell and Burcham [] about the limit of small structure drifts to the ion‐acoustic speed ( C s ). The simulation results of the unified fluid model presented in the previous work [ Hassan et al , and Hassan , ] and the present work show a very good agreement with these radar measurements.…”
Section: Introductionsupporting
confidence: 88%
“…As noted above, in the previous work of Hassan et al [] the 2‐D unified fluid model that unifies the Farley‐Buneman and gradient‐drift instabilities was derived. There it was shown that this model has linear results that are comparable to the kinetic treatment of the Farley‐Buneman plasma instability by Schmidt and Gary [], and simulation results also showed good agreement with the radar measurements and sounding rocket observations.…”
Section: Unified Fluid Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…2, where the phase velocity is calculated at different altitudes using nonlocal magnitudes of the ionospheric background. 18,19 We still can see the three distinct regions of the equatorial electrojet with the exchange dominance and coupling between unstable waves of different scale-sizes that are generated as a result of the gradient-drift and Farley-Buneman instabilities. The maximum phase velocity is found at the core of the electrojet around 105 km has the same magnitude of the E × B drift velocity (400 m/s).…”
Section: A Growth-rate and Phase Velocitymentioning
confidence: 97%
“…4 to unify Farley-Buneman and gradient-drift instabilities in the equatorial electrojet. In that model, the plasma dynamics in the ion viscosity-tensor and electron polarization drifts were considered to play an important role in stabilizing the evolving fields.…”
Section: B Equations Of Motionmentioning
confidence: 99%